This is why you dream : what your sleeping brain reveals about your waking life - Jandial, Rahul (Penguin Life, 2024)
"A fascinating dive into the purpose and potential of dreams Dreaming is one of the most deeply misunderstood functions of the human brain. Yet recent science reveals that our very survival as a species has depended on it. This Is Why You Dream explores the landscape of our subconscious, showing why humans have retained the ability to dream across millennia and how we can now harness its wondrous powers in both our sleeping and waking lives. Dreaming fortifies our ability to regulate emotions. It processes and stores memories, amplifies creativity, and promotes learning. Dreams can even forecast future mental and physical ailments. Dreams can also be put to use. Tracing recent cutting-edge dream research and brain science, dual-trained neuroscientist and neurosurgeon Dr. Rahul Jandial shows how to use lucid dreaming to practice real-life skills, how to rewrite nightmares, what our dreams reveal about our deepest desires, and how to monitor dreams for signs of Parkinson's and Alzheimer's. In the tradition of James Nestor's Breath and Matthew Walker's Why We Sleep, This Is Why You Dream opens the door to one of our oldest and most vital functions, and unlocks its potential to impact and radically improve our lives"--